Relationship between Work Connectivity Behavior After-hours and Job Satisfaction: An Empirical Study on Frontier Employees in Chinese Enterprises - Dai, Ziyue; Wang, Yuhe; Zheng, Hanyu (Transactions on Economics, Business and Management Research, 2024)
Now highly competitive business environment in today’s world, Chinese enterprises are constantly seeking ways to improve their own competitiveness. Employee satisfaction is a key factor in determining the success of an enterprise. This research aims to quantitatively explore the relationship between work connectivity behavior after-hours and job satisfaction among frontier employees in Chinese enterprises. The study focuses on this specific group of employees. By employing multiple linear regression for data analysis, it precisely measures the connection between these two factors. Rigorous data analysis reveals that work connectivity behavior after-hours has no significant impact on job satisfaction. The findings of this study can assist Chinese enterprises in formulating more targeted human resource policies to enhance the job satisfaction of frontier employees and provide valuable experience and references for relevant enterprise management strategies. Finally, the conclusion is that after-hours work connectivity behavior has no substantial impact on the job satisfaction of frontier employees in enterprises in China. Based on the research conclusions, the following revelations can be drawn: Chinese enterprises should pay attention to improving employees' material conditions, especially the salary level. They should provide appropriate salary incentives for front-line employees to enhance their job satisfaction. At the same time, Chinese enterprises should implement different management methods for front-line employees of different ages to achieve flexible employment and management and thereby improve employees' job satisfaction.